Humidity sensing using THz metamaterial with silk protein fibroin - Hwan, Sik Kim; Sung, Ho Cha; Roy, Biswajit; Kim, Sunghwan; Ahn, Y. H. (Optics Express, 2018)
In this study, we developed hybrid humidity sensing methods by incorporating silk fibroin protein onto metamaterials, operating in the terahertz (THz) frequencies; the resonant frequency shifted but saturated at a specific thickness due to the limited sensing volume of the metamaterial. From the saturated value, we extracted the dielectric constant for the silk films. We also observed additional resonance shifts when we applied humid air to silk-coated metamaterials, due to the increased water molecule numbers on the film. Frequency shifts depend linearly on relative humidity. Also, in situ THz spectroscopy measurements reveal that the time response is instantaneous within our detection limit, especially upon exposure to humid air, whereas the small slowly decaying component appeared when we applied dry air. The time taken by the slow component in the drying process was 10–50 s, depending on film thickness. This could optimize humidity sensors as a fast and efficient detection tool to measure air humidity.
Keywords: Detection limits; Efficient detection; Frequency shift; Humidity sensing; Resonance shift; Slow component; Terahertz frequencies; Thz spectroscopy; Fibroins; Humidity; Limit of Detection; Silk; Terahertz Spectroscopy; Water